Specific sequence mutations in a long-lasting rhIFN-α2b version reduce in vitro and in vivo immunogenicity and increase in vitro protein stability - Eduardo Federico Mufarrege; Lucía Carolina Peña; Marina Etcheverrigaray; Anne S. De Groot; William Martin (Heliyon, 2023)
For decades, recombinant human interferon alpha (rhIFN-α2b) has been used to treat emerging and chronic viral diseases. However, rhIFN-α2b is immunogenic and has a short in vivo half-life. To solve these limitations, two long-lasting hyperglycosylated proteins with reduced immunogenicity were developed and designated as 4N-IFN(VAR1) and 4N-IFN(VAR3).Here, we continue to study the relevant characteristics of these therapeutic candidates. Thus, we demonstrated that both de-immunized IFN versions elicited significantly lower neutralizing antibody responses than the original molecule in HLA-DR1 transgenic mice, confirming our previous in vitro protein immunogenicity data. Also, we found that these biobetters exhibited remarkable stability when exposed to different physical factors that the protein product may encounter during its production process and storage, such as low pH, thermal stress, and repeated freezing/thawing cycles. Taking into consideration our previous and present results, 4N-IFN(VAR1) and 4N-IFN-4N(VAR3) appear to be valuable candidates for the treatment of human viral diseases.